Analisa Pengaruh Desain 6 Fasa dengan Sistem 1 Lapis dan 3 Medan Fluks pada Motor Induksi 3 Fasa Terhadap Torsi dan Kecepatan Motor - Dolly Yoga Pratama Rambe; Zuriman Anthony; Erhaneli Erhaneli; Arfita Yuana Dewi; Zulkarnaeni Zulkarnaeni (Dinasti Research, 2023)
This study aims to examine the effect of a 6-phase design on the torque and speed of a 3-phase induction motor with a symmetrical single-layer design system. The research was conducted in the Power Systems Laboratory of Electrical Engineering, Padang Institute of Technology by continuing to operate a 3-phase induction motor with this 6-phase design in this 3-phase electric power system. Then it is compared with the performance of a conventional 3-phase induction motor and focuses on the torque and speed of the motor. The induction motors that are the object of research are 3-phase induction motors, 0.75 KW, 1 HP, 380 V/Y, 1.3A, 50 HZ, and 2880 RPM. The results of the study indicate that there is a decrease in torque in the 1-layer symmetrical 6-phase design motor with 3 flux fields due to a decrease in the ability of the motor with increasing speed. This is due to the occurrence of a flux field attached to one of the two coils which is serialized to the other 2 coils with different types of magnetic poles so that they weaken each other which affects the decrease in the ability to drive the motor so that the torque prod. used decreases